Nucleoside-modified VEGFC mRNA induces organ-specific lymphatic growth and reverses experimental lymphedema - Dániel Szőke (Nature Portfolio, 2021)
Dysfunction of the lymphatic system leads to secondary lymphedema and results in degradation of quality of life. Here, the authors show that delivery of nucleoside-modified Vascular Endothelial Growth Factor C (VEGFC) mRNA, encapsulated in lipid nanoparticles, induces organ-specific lymphatic growth and reverses experimental lymphedema.